Optimizing the separation characteristics of the waterinjection hydrocyclone using mathematical modelling - Minkov, Leonid; Dück, Johann; Hassan, Mohamed M. A.; Ali, Mahrous A. M.; Farghaly, Mohamed G. (Mining of Mineral Deposits, 2021)
Purpose. Although the hydrocyclone separator has many advantages, it still has some limitations which decrease its separation efficiency in many mineral processing applications because of fine particles which are miss separated to the coarse product in the underflow. Water injection in the conical part of the cyclone was recently implemented to solve this problem. The water injection mechanism and the way in which the injected water affects the separation are still not clear and need to be more investigated.
CRIS-Team WoS Importer:2022-01-14